Rilpivirine, emtricitabine and tenofovir alafenamide: single-tablet combination for the treatment of HIV-1 infection in selected patients. Issue 12 (1st December 2016) - Ogbuagu, Onyema
ABSTRACT: Introduction: Co-formulated rilpivirine, emtricitabine and tenofovir alafenamide (RPV/F/TAF) is the 6 th single-tablet combination antiretroviral medication approved within the past decade for the treatment of HIV-1 infection. It was approved based on positive bioequivalence studies with already approved drugs with its component compounds, RPV and the single tablet regimen- elvitegravir, cobicistat, F/TAF. Areas covered: This article reviews the chemical, pharmacodynamic and pharmacokinetic properties, key drug interactions, and the efficacy, safety, tolerability and optimal clinical uses of the medication and/or its components in different patient populations. The article incorporates pre-clinical and clinical trial data available from Google, Google scholar, PubMed database, conference abstracts as well as US FDA approved drug prescribing information up till September 30, 2016. Expert commentary: RPV/F/TAF is a once-daily administered, well tolerated, and effective antiretroviral regimen that should be taken with a meal. Desirable properties include less neuropsychiatric toxicity than 1 st generation non-nucleoside reverse transcriptase inhibitors, better bone and renal safety than tenofovir disoproxil fumarate containing regimens and it may be used in individuals with a creatinine clearance >30 mL/min. A five-year future view of the role of oral antiretroviral drug therapy as well as evolving treatment options for HIV-infected patients are also discussed in the article.